2017
DOI: 10.1155/2017/3695141
|View full text |Cite
|
Sign up to set email alerts
|

Multivariant Crystallization of Tetraplatin Precursors from Solutions Containing 1,2-C6H10(NH3)22+ and [PtCl6]2– Ions

Abstract: Seven new phases containing hexachloroplatinate [PtCl 6 ]2− and trans-1,2-dl-diammoniumcyclohexane 1,2-C 6 H 10 (NH 3 ) 2 2+ ions were obtained by crystallization from solutions with minor variation of synthesis conditions. The compounds can be applied as precursors for the synthesis of effective anticancer drug tetraplatin ([PtC 6 H 10 (NH 2 ) 2 Cl 4 ]). The phase diversity was achieved by alterations including solvent acidity, crystallization rate, temperature, type of solvent, and the reagents ratio. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…It has been reported that 1,2-C 6 H 10 (NH 3 ) 2 2+ will react with [PtCl 6 ] 2− to form [PtC 6 H 10 (NH 2 ) 2 Cl 4 ], most likely as a consequence of a Lewis acid–base interaction. 43 A similar Lewis acid–base interaction would be expected to occur between CH 3 CH 2 NH 3 + ( i.e. , intercalated EA in the EA/H x K 2− x LaTa 2 O 6 N) and [PtCl 6 ] 2− , thereby resulting in the sequential photodeposition of Pt.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that 1,2-C 6 H 10 (NH 3 ) 2 2+ will react with [PtCl 6 ] 2− to form [PtC 6 H 10 (NH 2 ) 2 Cl 4 ], most likely as a consequence of a Lewis acid–base interaction. 43 A similar Lewis acid–base interaction would be expected to occur between CH 3 CH 2 NH 3 + ( i.e. , intercalated EA in the EA/H x K 2− x LaTa 2 O 6 N) and [PtCl 6 ] 2− , thereby resulting in the sequential photodeposition of Pt.…”
Section: Resultsmentioning
confidence: 99%